Zircon geochronology and Hf isotopes of the silicic Panjal Traps: A window into the Himalayan basement rocks of the Pangea Megasequence - J. Gregory Shellnutt; Sam Uthup; Robert B.-J. Hsieh; Hao-Yang Lee (Gondwana Research, 2026)

Exciplex strength as a design principle for high-performance organic light-emitting diodes - Al Amin; Jee-Hun Jang; Woo-Sam Kim; Hanbeen Lee; Jaeho Lee; Rino Choi; Jeong-Hwan Lee (Chemical Engineering Journal, 2026)

Retraction notice to “Biochar for urban agriculture: Impacts on soil chemical characteristics and on Brassica rapa growth, nutrient content and metabolism over multiple growth cycles” [Sci. Total Environ. 727 (2020) 138742] - Shuang Song; Srishti Arora; Anna Karen C. Laserna; Ye Shen; Brian W.Y. Thian; Jia Chin Cheong; Jonathan K.N. Tan; Zhongyu Chiam; Siew Lee Fong; Subhadip Ghosh; Yong Sik Ok; Sam F.Y. Li; et al. (Science of The Total Environment, 2026)

Climatological Characteristics of Low-Level Jets over the Korean Peninsula Based on ERA5 Data - Kum-Lan Kim; Myoung-Seok Suh; Sang-Sam Lee (Asia-Pacific Journal of Atmospheric Sciences, 2026)

Effect of Temperature on Microbial Diversity and Predictive Function in the Intestine of Olive Flounder (Paralichthys olivaceus) - Hyun-Kyoung Jung; Eunkyung Choi; Hyejung Jung; Min-Kyeong Lee; Jungwook Park; Dong-Gyun Kim; Jung-Ha Kang; Young-Sam Kim (Fishes, 2026)
While the impact of the environment on the fish microbiome remains under discussion, studies on the intestinal bacterial diversity of olive flounder are still limited. This study investigated the effects of three temperature conditions, 15 °C (Group L), 20 °C (Group M), and 25 °C (Group H), on the structure and diversity of the bacterial community in the gut of olive flounder. During the 35-day experiment, changes were observed in the composition and diversity of the gut microbiota, with alpha diversity estimates gradually decreasing as the temperature increased. At the species level, there were significant differences in the relative abundance of Sphingomonas echinoides and Photobacterium damselae between Groups L and H. According to LEfSe and correlation analyses, the relative abundances of Gammaproteobacteria, Alphaproteobacteria, Sphingomonas, and Photobacterium varied significantly depending on temperature levels. Through functional prediction, the predicted functional pathways based on bacterial abundances showed that those involved in aromatic compound degradation and amino acid metabolism were abundant in Group L, whereas pathogenic factors were abundant in Group H, suggesting a potential impact on host digestive and immune functions. These results suggest that temperature can significantly affect both the diversity and potential functional profiles of the intestinal microbiota in olive flounder.

Expanded SSR profile database for forensic discrimination and phylogenetic analysis in cultivars of spring orchid (Cymbidium goeringii) - Kyung Suk Lee; Yu Bin Kim; Juha Kim; Sam-Geun Kong; Ki Wha Chung (Genes & Genomics, 2026)

Quantitative Cellular AGing Evaluation system (qCAGEs): a dual-parameter platform for high-throughput senescence screening - Dong-Ju Shin; Young-Sam Lee; Chong Won Choi; Hyun Ju Kang; Jin-Ku Lee (GeroScience, 2026)

Calibration-free on-site detection of microcystin-LR using integrated biosensing, multi-parameter water quality monitoring, and machine learning - Minjae Kim; Samuel Adjei-Nimoh; Jungsu Park; Sunday Sam Egon; Emmelyn Choi; Gijung Pak; Kwangtae You; A H M Anwar Sadmani; Keug Tae Kim; Woo Hyoung Lee (Water Research, 2026)

Hydrolysis patterns of enzymatically modified steviol glycosides - Myeong Ji Kim; Jeong-Eun Lee; Young-Sam Keum; Hyunwoo Kim (Food Chemistry, 2026)

Innovative upgrading pathways for the one-pot conversion of biomass and related substrates to alkyl levulinates: advancements and optimization - Soolim Kim; Sam Yeol Lim; Dong-Jun Lee; Sungyup Jung; Jechan Lee (Chemical Engineering Journal, 2026)

Dual ligand (2MI/BI) promoting graphitic ordering and nitrogen enrichment in Fe-activated carbon nanofibers for freestanding flexible supercapacitors - Ashwin Khadka; Bhavana Joshi; Edmund Samuel; Kukhee Park; Seung-kug Kim; Mira Park; Hae-Seok Lee; Sam S. Yoon (Chemical Engineering Journal, 2026)

Engineering multifunctional thin-film composite polyamide membranes with water-soluble amphiphilic cationic block copolymer surfactants by regulating interfacial polymerization - Jae Jun Kim; Sokhuoy Sam; Doseok Kim; Jong-Chan Lee (Chemical Engineering Journal, 2026)

New Zealand blackcurrant extract has no effect on physiological and cardiovascular responses during low-intensity sustained intermittent isometric contractions in men - Stefano Montanari; Ben J. Lee; Sam D. Blacker; Matthew D. Cook; Mark E. T. Willems (European Journal of Applied Physiology, 2026)

Myosin light chain kinase 2 and Myomesin 2 are related to the stiffness of vocal fold lamina propria in aging rats and humans - Ji-Min Kim; Hyoung-Sam Heo; Hyoun-Wook Lee; Gi-Cheol Park; Sung-Chan Shin; Yong-il Cheon; Ha-Nee Kwon; Byung-Joo Lee (Biogerontology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Antimicrobial resistance, genomic, and public health insights into Enterococcus spp. from Australian cattle - Rebecca Abraham; Shafi Sahibzada; Terence Lee; David Jordan; Kate McMillan; Glen Mellor; Lesley Duffy; Kittitat Lugsomya; Mark O'Dea; Sam Abraham; Robert Barlow (Veterinary Microbiology, 2026)

Textile waste upcycling into air-cathode for microbial fuel cell with energy recovery - Yeonju Jeong; Sam Yeol Lim; Jechan Lee; Gahyun Baek (Environmental Research, 2026)

Genomic prediction accuracy in Korean Holstein population: A comprehensive study of milk production traits - Md Azizul Haque; You-Sam Kim; Chang-Gwon Dang; Yun-Mi Lee; Jong-Joo Kim (The Veterinary Journal, 2025)

Chia seed mucilage biosorbent synergism with hydrophobic iron (III)-natural phenolic nanoparticles for dispersive solid-phase extraction of tetracycline residues in milk and honey samples before HPLC analysis - Nongnapas Nakhonchai; Kraingkrai Ponhong; Jonathan V. Sweedler; Chang Young Lee; Sam-ang Supharoek (Food Chemistry, 2025)

Golden Oyster Mushroom Extract Ameliorates Oxidative Stress-Induced Cell Death in Neurons and Scopolamine-Induced Cholinergic System Impairment in Mice - Ho-Sung Ryu; Sanjay; Sung-Keun Choi; Kun-Hee Lee; Sung-Soo Jang; Su-Yeon Yang; Young-Sam Kwon; Sae-Kwang Ku; Hae-Jeung Lee (Molecular Neurobiology, 2025)

Evaluating projections of the costs of pesticide regulation: Evidence from California's chlorpyrifos withdrawal - Benjamin W Lee; Kevi Mace; James Keeler; Sam Raburn; Daniel Schuurman; Yanan Zheng; Rachael Goodhue (Agricultural Systems, 2025)

Hwangkeumjakyak-tang protects against hepatocyte damage via oxidative stress inhibition and affects the altered gut microbiome pattern in acetaminophen-induced liver injury - Sam Seok Cho; So Hi Kang; Jeon Kyung Kim; Yu Bin Lee; Hong Seok Son; Jae Min Kim; Chang Su Na; Ji Hye Yang (Advances in Traditional Medicine, 2025)
Hwangkeumjakyak-tang (HJT), a Korean traditional herbal medicine, is known to clear phlegm, relieve congestion, and reduce inflammation. However, there is a lack of research on the efficacy of HJT in other diseases. The present study aimed to investigate whether HJT could protect against liver injury. We first examined the effects of HIT in vitro by assessing its toxicity and the phosphorylation and nuclear translocation of nuclear factor erythroid 2-related factor 2 (Nrf2) in human HepG2 cells. Additionally, we investigated whether HJT inhibited oxidative stress by measuring reactive oxygen species (ROS) production and intracellular levels of reduced glutathione (GSH). We further assessed the effects of HJT in vivo by analyzing liver damage parameters using an acetaminophen (APAP)-induced liver damage mouse model. Treatment with HJT significantly reduced the elevated serum levels of ALT and AST and the cytokine release induced by APAP injection. Furthermore, we verified that treatment with HJT suppressed APAP-induced ROS production and GSH depletion in the mouse liver, suggesting that HJT inhibited APAP-induced liver injury by blocking oxidative stress in vivo. To identify the potential relationship between the liver and intestine for liver disease therapy, we also performed 16S rRNA amplicon sequencing to analyze the gut microbiome and confirmed that HJT regulated APAP-induced changes in the gut microbiome pattern. In conclusion, HJT, a Nrf2 activation inducer, exhibits a cytoprotective effect on APAP-induced liver injury and can regulate the gut microbiome altered by the administration of APAP.

Spatial variation and habitat preference of reef fish and gastropod assemblages from two coastal habitats in subtropical reef, Port Shelter, Hong Kong - Sam King Fung Yiu; Thomas Ka Tung Leung; Gabriel Yeung Lee; Meng Yan (Marine Environmental Research, 2025)

Drivers of carbon accumulation in eucalypt plantations: a multivariate analysis and prediction models for Australian and Brazilian experiments - Juliana Campos Amorim; João Marcos Rebessi de Sousa; Fábio Prataviera; Paulo Henrique Müller da Silva; Sérgio Augusto Rodrigues; Sam Van Holsbeeck; Saulo Philipe Sebastião Guerra; David J. Lee; Humberto de Jesus Eufrade-Junior (New Forests, 2025)

Strain-Specific Effects of Bacillus subtilis, Enterococcus faecium, and Pediococcus pentosaceus Supplementation on Growth Performance, Immunity, and Disease Resistance in Olive Flounder (Paralichthys olivaceus) - Min-Kyeong Lee; Hyun-Kyoung Jung; Dong-Gyun Kim; In-Suk Park; Yu Li Heo; Jungha Kang; Young Sam Kim (Fishes, 2025)
Olive flounder (Paralichthys olivaceus), a key aquaculture species in East Asia, is prone to stress and bacterial diseases under intensive farming. Antibiotics are often used to control these problems, but their overuse promotes resistance and threatens sustainability. To provide safer alternatives, this study evaluated the strain-specific effects of dietary probiotics on growth, immunity, and disease resistance in olive flounder. A five-week feeding trial was conducted to evaluate the effects of three isolates—Bacillus subtilis, Enterococcus faecium, and Pediococcus pentosaceus—on growth, blood biochemistry, immune responses, and resistance against Edwardsiella tarda. Each strain was incorporated individually into a basal diet. After the feeding trial, probiotic supplementation improved growth performance. P. pentosaceus significantly increased final body weight and other growth indices (p

NextGen In A Box (NGIAB): Open-Source containerization of the NextGen framework to enable community-driven hydrology modeling - Arpita Patel; James Halgren; Zach Wills; Nels Frazier; Benjamin Lee; Joshua Cunningham; Jordan Laser; Mohammadsepehr Karimiziarani; Trupesh Patel; Giovanni Romero; Matthew Denno; Sam Lamont; et al. (Environmental Modelling & Software, 2025)

Evaluating the Trophic Structure of an Artificial Macroalgal Bed of Eisenia bicyclis Using C and N Stable Isotopes - Dong-Young Lee; Dongyoung Kim; Chan-Kil Chun; Youngkweon Lee; Kyu-Sam Han; Hyun Kyum Kim; Tae Hee Park; Hyun Je Park (Journal of Marine Science and Engineering, 2025)
In this study, we applied a new technique for vegetatively transplanting kelp Eisenia bicyclis to restore macroalgal habitats. We aimed to assess the restoration success of the E. bicyclis bed by comparing the carbon and nitrogen stable isotope ratios of macrobenthic consumers and their isotopic niches in artificial and control (barren ground) habitats. Except for the deposit feeding group, no significant differences were observed in isotopic values of the other feeding groups (suspension feeders, herbivores, omnivores, and carnivores) between the two sites. In contrast, our results showed wider isotopic niche indices for all feeding groups at the transplantation site compared to those at the control site, suggesting increased trophic diversity in the artificial habitat. Overall, these results indicate that the macroalgal bed created using the new method can play an ecological role in restoring functional properties of food web structures via trophic support of degraded coastal ecosystems.

West Nile virus in Culex mosquitoes and dead birds from the San Gabriel Valley, California, 2021–2022 - Christine A. Mariskanish; Tristan Hallum; Sam S. Lee; Christian K. Fung; Thomas R. Tchingambu; Matthew A. Conte; Jun Hang (Archives of Virology, 2025)

Formulation Development and Characterization of Bigels Containing Curcumin for Topical Skin Delivery - Lord Sam Liston; Suranate Phanapithakkun; Nuttakul Pimsarn; Nuttapon Dangkaokhia; Thanat Nakasan; Attawadee Sae Yoon; Hiroaki Todo; Teerapol Srichana; Somchai Sawatdee; Gerard Lee See; Florencio Arce; Pajaree Sakdiset (AAPS PharmSciTech, 2025)

Refining the known extent of major onshore Quaternary glaciation in the UK — Types of evidence, nomenclature and uncertainty - Jonathan R. Lee; Sam Roberson (Proceedings of the Geologists' Association, 2025)

Climatology of Low-Level Jets of Korea from Long-Term Rawinsonde Observations - Kum-Lan Kim; Myoung-Seok Suh; Sang-Sam Lee (Asia-Pacific Journal of Atmospheric Sciences, 2025)

End-of-life vehicle plastic management in Republic of Korea: Material flow analysis and hazardous substance analysis - Sun-Ju Lee; Na-Hyeon Cho; Young-Sam Yoon; Tae-Wan Jeon; Woori Cho; Seungtaek Lee; Young-Yeul Kang (Resources, Conservation and Recycling, 2025)

Corrigendum to “Acidic polysaccharide from the edible insect Protaetia brevitarsis seulensis activates antiviral immunity to suppress norovirus infection” [Carbohydrate Polymers 347 (2025) 122587] - Ibukunoluwa Fola Olawuyi; Eun Heo; Minju Jeong; Jae Hwan Kim; Jong-Jin Park; Jongbeom Chae; Subin Gwon; Seong Do Lee; Hunseong Kim; Oyindamola Vivian Ojulari; Young-Bo Song; Byung-Hoo Lee; et al. (Carbohydrate Polymers, 2025)

Corrigendum to “Acidic polysaccharide from the edible insect Protaetia brevitarsis seulensis activates antiviral immunity to suppress norovirus infection” [Carbohydrate Polymers, Volume 347 (2025), Article Number 122587] - Ibukunoluwa Fola Olawuyi; Eun Heo; Minju Jeong; Jae Hwan Kim; Jong-Jin Park; Jongbeom Chae; Subin Gwon; Seong Do Lee; Hunseong Kim; Oyindamola Vivian Ojulari; Young-Bo Song; Byung-Hoo Lee; et al. (Carbohydrate Polymers, 2025)

Flexible freestanding carbon nanofiber mats decorated with Zn/Co oxide nanostructures derived from zeolitic imidazolate frameworks as supercapacitor electrodes - Jungwoo Huh; Mayagozel Abdyrahymova; Bhavana Joshi; Edmund Samuel; Ali Aldalbahi; Mostafizur Rahaman; Heejin Kim; Min Wook Lee; Sam S. Yoon (Chemical Engineering Journal, 2025)

Acidic polysaccharide from the edible insect Protaetia brevitarsis seulensis activates antiviral immunity to suppress norovirus infection - Ibukunoluwa Fola Olawuyi; Eun Heo; Minju Jeong; Jae Hwan Kim; Jong-Jin Park; Jongbeom Chae; Subin Gwon; Seong Do Lee; Hunseong Kim; Oyindamola Vivian Ojulari; Young-Bo Song; Byung-Hoo Lee; et al. (Carbohydrate Polymers, 2025)

Spectral induced polarization (SIP) measurements across a PFAS-contaminated source zone - Ethan Siegenthaler; Sam Falzone; Charles Schaefer; Dale Werkema; Lee Slater (Journal of Hazardous Materials, 2024)

Effects of Late-Passage Small Umbilical Cord–Derived Fast Proliferating Cells on Tenocytes from Degenerative Rotator Cuff Tears under an Interleukin 1β-Induced Tendinopathic Environment - Ah-Young Lee; Ju-Young Park; Sam Joongwon Hwang; Kwi-Hoon Jang; Chris Hyunchul Jo (Tissue Engineering and Regenerative Medicine, 2024)
Background Tendinopathy is a chronic tendon disease. Mesenchymal stem cells (MSCs), known for their anti-inflammatory properties, may lose effectiveness with extensive culturing. Previous research introduced “small umbilical cord–derived fast proliferating cells” (smumf cells), isolated using a novel minimal cube explant method. These cells maintained their MSC characteristics through long-term culture. Thus, the purpose of the present study was to assess the anti-inflammatory effects of late-passage smumf cells at P10 on tenocytes derived from degenerative rotator cuff tears in a tendinopathic environment. Methods The mRNA expression with respect to aging of MSCs and secretion of growth factors (GFs) by smumf cells at P10 were measured. mRNA and protein synthesis in tenocytes with respect to the tenocyte phenotype, inflammatory cytokines, and matrix- degradation enzymes were measured. The inflammatory signal pathways involving nuclear factor kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) in tenocytes were also investigated. The proliferative response of degenerative tenocytes to co-culture with smumf cells over 7 days in varying IL-1 β induced tendinopathic environments was investigated. Results smumf cells at P10 showed no signs of aging compared to those at P3. smumf cells at P10, secreting 2,043 pg/ml of hepatocyte growth factor (HGF), showed a 1.88-fold ( p = .002) increase in HGF secretion in a tendinopathic environment. Degenerative tenocytes co-cultured with smumf cells showed significantly increased protein expression levels of collagen type I (Col I) and the Col I/III ratio by 1.46-fold ( p < .001) and 1.66-fold ( p < .001), respectively. The smumf cells at P10 reduced both mRNA and protein expression levels of matrix metalloproteinases-1, -2, -3, -8, -9, and -13 in tenocytes and attenuated NF-κB (phosphorylated IκBα/IκBα and phosphorylated p65/p65) and MAPK (phosphorylated p38/p38 and phosphorylated JNK/JNK) pathways activated by IL-1 β . Removal of IL-1 β from the co-culture accelerated the growth of tenocytes by 1.42-fold ( p < .001). Removal of IL-1 β accelerated tenocyte growth in co-cultures. Conculsion Late-passage smumf cells exert anti-inflammatory effects on tenocytes derived from degenerative rotator cuff tears under a tendinopathic environment, primarily through the secretion of growth factors (GFs).

Feedstock recycling of polycarbonate waste via thermochemical conversion supported by municipal solid waste incinerator bottom ash - Sam Yeol Lim; Jechan Lee (Chemosphere, 2024)

Electrospun carbon/iron–vanadium oxide nanofibers for high energy density supercapacitors - Edmund Samuel; Ashwin Khadka; Bhavana Joshi; Hao Gao; Suraj More; Ali Aldalbahi; Govindasami Periyasami; Hae-Seok Lee; Bin Ding; Sam S. Yoon (Chemical Engineering Journal, 2024)

The Effect of Exercise on Mesenchymal Stem Cells and their Application in Obesity Treatment - Ying-Ying Xiang; Jong-Hwa Won; Sam-Jun Lee; Kyung-Wan Baek (Stem Cell Reviews and Reports, 2024)

Animal-free scaffold from brown algae provides a three-dimensional cell growth and differentiation environment for steak-like cultivated meat - Heejae Lee; Dasom Kim; Kyeong Hun Choi; Sangmin Lee; Minguk Jo; Song-Yi Chun; Yebin Son; Jong Ha Lee; Kwanhyeong Kim; TaeByung Lee; Joonho Keum; Min Yoon; et al. (Food Hydrocolloids, 2024)

Enabling factors and critical extensions for the algal-based bioplastics industry - Thomas Lee; Sam Wearne; Rachael Wakefield-Rann; Kate Scardifield (Journal of Cleaner Production, 2024)

Enhancement of recycling system for large WEEE plastics in Korea via material flow analysis (MFA) and hazardous substances assessment - Na-Hyeon Cho; Sun-Ju Lee; Young-Yeul Kang; Young-Sam Yoon; Tae-Wan Jeon (Resources, Conservation and Recycling, 2024)

A comparison of the nutritional quality of ready-to-cook meals and conventional home-cooked meals in Korea - Eunji Choi; Sung-Won Yoon; Jung-Ah Shin; In-Hwan Kim; Jeehye Sung; Jang-Hyuk Ahn; Hyun-Jeong Kim; Dong Won Seo; Sam-Pin Lee; Jo-Won Lee; Bo Kyung Moon; Sojung Kim; et al. (International Journal of Gastronomy and Food Science, 2024)

Recent developments and prospects of sustainable remediation treatments for major contaminants in soil: A review - H. Lee; K. Sam; F. Coulon; S. De Gisi; M. Notarnicola; C. Labianca (Science of The Total Environment, 2024)

Uniformly distributed FeVO4 nanocuboids on exfoliated rGO facilitated by supersonic spraying for wearable supercapacitors - Bhavana Joshi; Byeong-yeop Kim; Edmund Samuel; Jungwoo Huh; Ali Aldalbahi; Mohamed El-Newehy; Hae-Seok Lee; Sam S. Yoon (Chemical Engineering Journal, 2024)

A hyperelastic adhesive forming multiple neutral planes even at extreme temperatures - Kihoon Jeong; Dohun Kim; Dahye Ahn; Chanhee Yang; Junmo Kim; Changhyeon Lee; Youson Kim; Chungryeol Lee; Young-Sam Park; Seung-Hyun Lee; Taek-Soo Kim; Sung Gap Im (Chemical Engineering Journal, 2024)

Early life PM2.5 exposure, childhood cognitive ability and mortality between age 11 and 86: A record-linkage life-course study from Scotland - Gergő Baranyi; Lee Williamson; Zhiqiang Feng; Sam Tomlinson; Massimo Vieno; Chris Dibben (Environmental Research, 2023)

Enhancing Viability of Human Embryonic Stem Cells during Cryopreservation via RGD-REP-Mediated Activation of FAK/AKT/FoxO3a Signaling Pathway - Jeong Hee Kim; Jeong In Choi; Young Hyun Che; Su Haeng Sung; Hojae Lee; Sun Lee; Jae-Hoon Park; Yun-Il Lee; Young-Sam Lee; Won Bae Jeon; Yong Jun Kim (Tissue Engineering and Regenerative Medicine, 2023)

Intra-urban Variations of the CO2 Fluxes at the Surface-Atmosphere Interface in the Seoul Metropolitan Area - Seon-Ok Hong; Jinwon Kim; Young-Hwa Byun; Jinkyu Hong; Je-Woo Hong; Keunmin Lee; Young-San Park; Sang-Sam Lee; Yeon-Hee Kim (Asia-Pacific Journal of Atmospheric Sciences, 2023)
Severe spatiotemporal heterogeneity of emissions sources and limited measurement networks have been hampering the monitoring and understanding of CO 2 fluxes in large cities, a great concern in climate research as big cities are among the major sources of anthropogenic CO 2 in the climate system. To understand the CO 2 fluxes in Seoul, Korea, CO 2 fluxes at eight surface energy balance sites, six urban (vegetation-area fraction 60%), for 2017–2018 are analyzed and attributed to the local land-use and business types. The analyses show that the CO 2 flux variations at the suburban sites are mainly driven by vegetation and that the CO 2 flux differences between the urban and suburban sites originate from the differences in the vegetation-area fraction and anthropogenic CO 2 emissions. For the CO 2 fluxes at the urban sites; (1) vehicle traffic (traffic) and heating-fuel consumption (heating) contribute > 80% to the total, (2) vegetation effects are minimal, (3) the seasonal cycle is driven mainly by heating, (4) the contribution of heating is positively related to the building-area fraction, (5) the annual total is positively (negatively) correlated with the commercial-area (residential-area) fraction, and (6) the traffic at the commercial sites depend further on the main business types to induce distinct CO 2 flux weekly cycles. This study shows that understanding and estimation of CO2 fluxes in large urban areas require careful site selections and analyses based on detailed consideration of the land-use and business types refined beyond the single representative land-use type widely-used in contemporary studies.

Proximity to human settlement is directly related to carriage of critically important antimicrobial-resistant Escherichia coli and Klebsiella pneumoniae in Silver Gulls - Shewli Mukerji; Shafi Sahibzada; Rebecca Abraham; Marc Stegger; David Jordan; David J. Hampson; Mark O’Dea; Terence Lee; Sam Abraham (Veterinary Microbiology, 2023)

Partitioning the forms of genotype-by-environment interaction in the reaction norm analysis of stability - Dominic L. Waters; Julius H. J. van der Werf; Hannah Robinson; Lee T. Hickey; Sam A. Clark (Theoretical and Applied Genetics, 2023)
Key message The reaction norm analysis of stability can be enhanced by partitioning the contribution of different types of G × E to the variation in slope. Abstract The slope of regression in a reaction norm model, where the performance of a genotype is regressed over an environmental covariable, is often used as a measure of stability of genotype performance. This method could be developed further by partitioning variation in the slope of regression into the two sources of genotype-by-environment interaction (G × E) which cause it: scale-type G × E (heterogeneity of variance) and rank-type G × E (heterogeneity of correlation). Because the two types of G × E have very different properties, separating their effect would enable a clearer understanding of stability. The aim of this paper was to demonstrate two methods which seek to achieve this in reaction norm models. Reaction norm models were fit to yield data from a multi-environment trial in Barley ( Hordeum vulgare ), with the adjusted mean yield from each environment used as the environmental covariable. Stability estimated from factor-analytic models, which can disentangle the two types of G × E and estimate stability based on rank-type G × E, was used for comparison. Adjusting the reaction norm slope to account for scale-type G × E using a genetic regression more than tripled the correlation with factor-analytic estimates of stability (0.24–0.26 to 0.80–0.85), indicating that it removed variation in the reaction norm slope that originated from scale-type G × E. A standardisation procedure had a more modest increase (055–0.59) but could be useful when curvilinear reaction norms are required. Analyses which use reaction norms to explore the stability of genotypes could gain additional insight into the mechanisms of stability by applying the methods outlined in this study.

Exploring the potential of MIL-derived nanocomposites to enhance performance of lithium-ion batteries - Bhavana Joshi; Edmund Samuel; Yong-Il Kim; Hae-Seok Lee; Mark T. Swihart; Sam S. Yoon (Chemical Engineering Journal, 2023)

Improvement of Korea Meteorological Administration Solar Energy Resources Map Using Fine-Scale Terrain Data - Jinah Yun; Jinwon Kim; Minwoo Choi; Hee-Wook Choi; Yeon-Hee Kim; Sang-Sam Lee (Asia-Pacific Journal of Atmospheric Sciences, 2023)
Real-time solar energy resources mapping is crucial for the development and management of solar power facilities. This study analyzes the effects of the digital elevation model (DEM) resolution on the accuracy of the surface insolation (insolation hereafter) calculated by the Korea Meteorological Administration solar energy mapping system, KMAP-Solar, using two DEMs of different resolutions, 1.5 km and 100 m. It is found that KMAP-Solar yields smaller land-mean insolation with the fine-scale DEM than the coarse-scale DEM. The fine-scale DEM reduces biases by as much as 32 Wm − 2 for all observation sites, especially those in complex terrain and that the insolation error reduction is correlated with the difference in sky view factor (SVF) between the coarse- and fine-scale DEM. Both the coarse- and fine-scale DEMs generate the insolation-elevation and insolation-SVF relationship which is characterized by positive (negative) correlation between the insolation and the terrain altitude (SVF). However, the coarse-scale DEM substantially underestimates these relationships compared to the fine-scale DEM, mainly because the coarse-scale DEM underrepresents large terrain slopes and/or small SVFs, most seriously in high-altitude regions. The fine-scale DEM generates a more realistic insolation distribution than the coarse-scale DEM by incorporating a wider range of key terrain parameters involved in determining insolation. Improvements of insolation calculations in KMAP-Solar using a fine-scale DEM, especially in the areas of complex terrain, is of a practical value for Korea because the operational solar resources map from KMAP-Solar supports solar energy research, solar power plant installations, and real-time prediction and management of solar power within the power grid.

The association of COVID-19 incidence with temperature, humidity, and UV radiation – A global multi-city analysis - Luise Nottmeyer; Ben Armstrong; Rachel Lowe; Sam Abbott; Sophie Meakin; Kathleen M. O'Reilly; Rosa von Borries; Rochelle Schneider; Dominic Royé; Masahiro Hashizume; Mathilde Pascal; Aurelio Tobias; et al. (Science of The Total Environment, 2023)

Thermally stable and soft pressure-sensitive adhesive for foldable electronics - Woosung Jo; Kihoon Jeong; Young-Sam Park; Jeong-Ik Lee; Sung Gap Im; Taek-Soo Kim (Chemical Engineering Journal, 2023)

Limited recovery following a massive seagrass decline in subarctic eastern Canada - Mélanie‐Louise Leblanc; Mary I. O'Connor; Zou Zou A. Kuzyk; Fanny Noisette; Kaleigh E. Davis; Ernie Rabbitskin; Laura‐Lee Sam; Urs Neumeier; Rémi Costanzo; Jens K. Ehn; David Babb; C. Julián Idrobo; et al. (Global Change Biology, 2023)
Over the last few decades, there has been an increasing recognition for seagrasses' contribution to the functioning of nearshore ecosystems and climate change mitigation. Nevertheless, seagrass ecosystems have been deteriorating globally at an accelerating rate during recent decades. In 2017, research into the condition of eelgrass ( Zostera marina ) along the eastern coast of James Bay, Canada, was initiated in response to reports of eelgrass decline by the Cree First Nations of Eeyou Istchee. As part of this research, we compiled and analyzed two decades of eelgrass cover data and three decades of eelgrass monitoring data (biomass and density) to detect changes and assess possible environmental drivers. We detected a major decline in eelgrass condition between 1995 and 1999, which encompassed the entire east coast of James Bay. Surveys conducted in 2019 and 2020 indicated limited changes post‐decline, for example, low eelgrass cover ( 50% cover in eastern James Bay since 1995, representing the largest scale eelgrass decline documented in eastern Canada since the massive die‐off event that occurred in the 1930s along the North Atlantic coast. Using biomass data collected since 1982, but geographically limited to the sector of the coast near the regulated La Grande River, generalized additive modeling revealed eelgrass meadows are affected by local sea surface temperature, early ice breakup, and higher summer freshwater discharge. Our results caution against assuming subarctic seagrass ecosystems have avoided recent global declines or will benefit from ongoing climate warming.

Cognitive performance in a South African cohort of people with HIV and comorbid major depressive disorder - Anna J. Dreyer; Sam Nightingale; Lena S. Andersen; Jasper S. Lee; Hetta Gouse; Steven A. Safren; Conall O’Cleirigh; Kevin G. F. Thomas; John Joska (Journal of NeuroVirology, 2022)

Crop rotation affects biological properties of rhizosphere soil and productivity of Kimchi cabbage (Brassica rapa ssp. pekinensis) compared to monoculture - Gye-ryeong Bak; Gye-jun Lee; Jung-tae Lee; Sam-nyu Jee (Horticulture, Environment, and Biotechnology, 2022)

Clear consensus among international public for government action at COP26: patriotic and public health frames produce marginal gains in support - Tessa Buchanan; James Ackland; Sam Lloyd; Sander van der Linden; Lee de-Wit (Climatic Change, 2022)

Uncovering Antimicrobial Peptide from Zophobas atratus Using Transcriptome Analysis - Joon Ha Lee; Hoyong Chung; Yong Pyo Shin; Mi-Ae Kim; Sathishkumar Natarajan; Karpagam Veerappan; Seong Hyun Kim; Junhyung Park; Jae Sam Hwang (International Journal of Peptide Research and Therapeutics, 2021)

dinF Elicits Nitric Oxide Signaling Induced by Periplanetasin-4 from American Cockroach in Escherichia coli - Heejeong Lee; Jae Sam Hwang; Dong Gun Lee (Current Microbiology, 2021)

Fine root dynamics across pantropical rainforest ecosystems - Walter Huaraca Huasco; Terhi Riutta; Cécile A. J. Girardin; Fernando Hancco Pacha; Beisit L. Puma Vilca; Sam Moore; Sami W. Rifai; Jhon del Aguila‐Pasquel; Alejandro Araujo Murakami; Renata Freitag; Alexandra C. Morel; Sheleme Demissie; et al. (Global Change Biology, 2021)
Fine roots constitute a significant component of the net primary productivity (NPP) of forest ecosystems but are much less studied than aboveground NPP. Comparisons across sites and regions are also hampered by inconsistent methodologies, especially in tropical areas. Here, we present a novel dataset of fine root biomass, productivity, residence time, and allocation in tropical old‐growth rainforest sites worldwide, measured using consistent methods, and examine how these variables are related to consistently determined soil and climatic characteristics. Our pantropical dataset spans intensive monitoring plots in lowland (wet, semi‐deciduous, and deciduous) and montane tropical forests in South America, Africa, and Southeast Asia ( n = 47). Large spatial variation in fine root dynamics was observed across montane and lowland forest types. In lowland forests, we found a strong positive linear relationship between fine root productivity and sand content, this relationship was even stronger when we considered the fractional allocation of total NPP to fine roots, demonstrating that understanding allocation adds explanatory power to understanding fine root productivity and total NPP. Fine root residence time was a function of multiple factors: soil sand content, soil pH, and maximum water deficit, with longest residence times in acidic, sandy, and water‐stressed soils. In tropical montane forests, on the other hand, a different set of relationships prevailed, highlighting the very different nature of montane and lowland forest biomes. Root productivity was a strong positive linear function of mean annual temperature, root residence time was a strong positive function of soil nitrogen content in montane forests, and lastly decreasing soil P content increased allocation of productivity to fine roots. In contrast to the lowlands, environmental conditions were a better predictor for fine root productivity than for fractional allocation of total NPP to fine roots, suggesting that root productivity is a particularly strong driver of NPP allocation in tropical mountain regions.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Evaluating the Ecological Benefits of Management Actions to Complement Environmental Flows in River Systems - Sam Nicol; J. Angus Webb; Rebecca E. Lester; Marcus Cooling; Paul Brown; Ian Cresswell; Heather M. McGinness; Susan M. Cuddy; Lee J. Baumgartner; Daryl Nielsen; Martin Mallen-Cooper; Danial Stratford (Environmental Management, 2021)

Inhibition of oxidative stress induced-cytotoxicity by coptisine in V79-4 Chinese hamster lung fibroblasts through the induction of Nrf-2 mediated HO-1 expression - Hyeon-Gyun Jo; Cheol Park; Hyesook Lee; Gi-Young Kim; Young-Sam Keum; Jin Won Hyun; Taeg Kyu Kwon; Yung Hyun Choi; Su Hyun Hong (Genes & Genomics, 2021)

Diversity of subtidal benthic and hard coral communities on sloping and vertical seawalls in Singapore - Y. P. Kikuzawa; C. S. L. Ng; T. C. Toh; S. Q. Sam; Y-L. Lee; P. L. Loo; Y. Z. Chua; K. S. Tan; L. M. Chou (Marine Biodiversity, 2020)

Male-Specific and Somatic Coliphage Profiles from Major Aquaculture Areas in Republic of Korea - JaeYoon Lee; SungJun Park; Cheonghoon Lee; Kyuseon Cho; Yong Seok Jeong; Young-Mog Kim; Kwon-Sam Park; Jong Duck Choi; Yongsik Sin; GwangPyo Ko (Food and Environmental Virology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Lessons from the past, policies for the future: resilience and sustainability in past crises - John Haldon; Merle Eisenberg; Lee Mordechai; Adam Izdebski; Sam White (Environment Systems and Decisions, 2020)

Adverse health risk from prolonged consumption of formaldehyde-preserved carps in eastern region of Indian population - Amit Kundu; Prasanta Dey; Rammohan Bera; Ratul Sarkar; Boomin Kim; Sam Kacew; Byung Mu Lee; Sanmoy Karmakar; Hyung Sik Kim (Environmental Science and Pollution Research, 2020)

Cardiac adaptation to exercise training in health and disease - Dae Yun Seo; Hyo-Bum Kwak; Amy Hyein Kim; Se Hwan Park; Jun Won Heo; Hyoung Kyu Kim; Jeong Rim Ko; Sam Jun Lee; Hyun Seok Bang; Jun Woo Sim; Min Kim; Jin Han (Pflügers Archiv - European Journal of Physiology, 2020)

Aerosol Physical Characteristics over the Yellow Sea During the KORUS-AQ Field Campaign: Observations and Air Quality Model Simulations - Yun-Kyu Lim; Jinwon Kim; Hee Choon Lee; Sang-Sam Lee; Joo-Wan Cha; Sang Boom Ryoo (Asia-Pacific Journal of Atmospheric Sciences, 2019)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Comparative toxicoproteogenomics of mouse and rat liver identifies TCDD-resistance genes - Stephenie D. Prokopec; Aileen Lu; Sandy Che-Eun S. Lee; Cindy Q. Yao; Ren X. Sun; John D. Watson; Rabah Soliymani; Richard de Borja; Ada Wong; Michelle Sam; Philip Zuzarte; John D. McPherson; et al. (Archives of Toxicology, 2019)

SEASTAR: A Mission to Study Ocean Submesoscale Dynamics and Small-Scale Atmosphere-Ocean Processes in Coastal, Shelf and Polar Seas - Christine Gommenginger; Bertrand Chapron; Andy Hogg; Christian Buckingham; Baylor Fox-Kemper; Leif Eriksson; Francois Soulat; Clément Ubelmann; Francisco Ocampo-Torres; Bruno Buongiorno Nardelli; David Griffin; Paco Lopez-Dekker; et al. (Frontiers in Marine Science, 2019)

Enhanced Transdermal Drug Delivery by Sonophoresis and Simultaneous Application of Sonophoresis and Iontophoresis - Juhyun Park; Hyowon Lee; Guei-Sam Lim; Nayoung Kim; Dongwon Kim; Yeu-Chun Kim (AAPS PharmSciTech, 2019)

Development and Evaluation of Hyaluronic Acid-Based Hybrid Bio-Ink for Tissue Regeneration - Jaeyeon Lee; Se-Hwan Lee; Byung Soo Kim; Young-Sam Cho; Yongdoo Park (Tissue Engineering and Regenerative Medicine, 2018)

Fabrication of Microchannels and Evaluation of Guided Vascularization in Biomimetic Hydrogels - Jaeyeon Lee; Se-Hwan Lee; Bu-Kyu Lee; Sang-Hyug Park; Young-Sam Cho; Yongdoo Park (Tissue Engineering and Regenerative Medicine, 2018)

Differential cellular responses by oncogenic levels of c-Myc expression in long-term confluent retinal pigment epithelial cells - Yiping Wang; Xiangdong Cheng; Muhammad Kaleem Samma; Sam K. P. Kung; Clement M. Lee; Sung Kay Chiu (Molecular and Cellular Biochemistry, 2018)

14-3-3β Depletion Drives a Senescence Program in Glioblastoma Cells Through the ERK/SKP2/p27 Pathway - Sung Bin Seo; Je-Jung Lee; Hye Hyeon Yun; Chang-Nim Im; Yong-Sam Kim; Jeong-Heon Ko; Jeong-Hwa Lee (Molecular Neurobiology, 2018)

Ionospheric delay gradient model for GBAS in the Asia-Pacific region - Susumu Saito; Surendra Sunda; Jiyun Lee; Sam Pullen; Slamet Supriadi; Takayuki Yoshihara; Michael Terkildsen; Frédéric Lecat (GPS Solutions, 2017)

Disease-associated change in an amphibian life-history trait - Benjamin C. Scheele; Lee F. Skerratt; David A. Hunter; Sam C. Banks; Jennifer C. Pierson; Don A. Driscoll; Philip G. Byrne; Lee Berger (Oecologia, 2017)

Autonomous CTD Profiling from the Robotic Oceanographic Surface Sampler - Jonathan Nash; June Marion; Nick McComb; Jasmine Nahorniak; Rebecca Jackson; Corwin Perren; Dylan Winters; Andy Pickering; Jorian Bruslind; Onn Lim Yong; Sam Lee (Oceanography, 2017)

Selenium-binding protein 1: a sensitive urinary biomarker to detect heavy metal-induced nephrotoxicity - Eui Kyung Lee; Young-Jun Shin; Eun Young Park; Nam Deuk Kim; Aree Moon; Seung Jun Kwack; Ji Yeon Son; Sam Kacew; Byung Mu Lee; Ok-Nam Bae; Hyung Sik Kim (Archives of Toxicology, 2017)

Behavioral responses of chinstrap and gentoo penguins to a stuffed skua and human nest intruders - Won Young Lee; Jin-Woo Jung; Han-Gu Choi; Hosung Chung; Yeong-Deok Han; Sam-Rae Cho; Jeong-Hoon Kim (Polar Biology, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Genetic and epigenetic cancer chemoprevention on molecular targets during multistage carcinogenesis - Hyung Sik Kim; Sam Kacew; Byung Mu Lee (Archives of Toxicology, 2016)

Scolopendin 2 leads to cellular stress response in Candida albicans - Heejeong Lee; Jae-Sam Hwang; Dong Gun Lee (Apoptosis, 2016)

Depletion of BIS sensitizes A549 cells to treatment with cisplatin - Mei Nu Cui; Hye-Hyeon Yun; Nan Ee Lee; Hye Yun Kim; Chang-Nim Im; Yong-Sam Kim; Jeong-Hwa Lee (Molecular & Cellular Toxicology, 2016)

Extreme Case Study of Quay Wall Stability under Earthquake and Tsunami - Kwang-Ho Lee; Do-Sam Kim; Tae-Hyung Kim (Marine Georesources & Geotechnology, 2015)

Genetic basis of age-dependent synaptic abnormalities in the retina - Hitoshi Higuchi; Erica L. Macke; Wei-Hua Lee; Sam A. Miller; James C. Xu; Sakae Ikeda; Akihiro Ikeda (Mammalian Genome, 2015)

A novel genetic variant database for Korean native cattle (Hanwoo): HanwooGDB - Kwondo Kim; Woori Kwak; Sam-Sun Sung; Seoae Cho; Heebal Kim; Duhak Yoon; Hyun-Jeong Lee (Genes & Genomics, 2015)

Analysis of degradation rate for dimensionless surface area of well-interconnected PCL scaffold via in-vitro accelerated degradation experiment - Se-Hwan Lee; Jun Hee Lee; Young-Sam Cho (Tissue Engineering and Regenerative Medicine, 2014)

Over 75 years of zooplankton data from Australia - Claire H. Davies; Amelia J. Armstrong; Mark Baird; Frank Coman; Steven Edgar; Daniel Gaughan; Jack Greenwood; Felipe Gusmão; Natasha Henschke; J. Anthony Koslow; Sophie C. Leterme; A. David McKinnon; et al. (Ecology, 2014)
Zooplankton are the key trophic link between primary producers and fish in pelagic ecosystems. Historically, there are few zooplankton time series in Australia, with no data sets longer than two years prior to 2008. Here we compile 98 676 abundance records of more than 1000 zooplankton taxa from unpublished research cruises, student projects, published literature, and the recent Integrated Marine Observing System (IMOS). This data set covers the entire coastal and shelf region of Australia and dates back to 1938. Most records are for copepods, but there are also data for other taxa such as decapods, chaetognaths, thaliaceans, appendicularians, and cladocerans. Metadata are provided for each record, including dates, coordinates, and information on mesh size and sampling methods. To facilitate analysis across the multiple data sets, we have updated the species names according to the World Register of Marine Species (WoRMS) and converted units to abundance per cubic meter. These data will be valuable for studies of biodiversity, biogeography, impacts of climate change, and ecosystem health. We encourage researchers holding additional Australian zooplankton data to contact us and contribute their data to the data set so we can periodically publish updates.

Antimicrobial peptides in the centipede Scolopendra subspinipes mutilans - Won Gi Yoo; Joon Ha Lee; Younhee Shin; Jae-Young Shim; Myunghee Jung; Byeong-Chul Kang; Jaedon Oh; Jiyeon Seong; Hak Kyo Lee; Hong Sik Kong; Ki-Duk Song; Eun-Young Yun; et al. (Functional & Integrative Genomics, 2014)

Fabrication of cylindrical PCL scaffolds using a knitting technique and assessment of cell proliferation in the scaffolds - A. Ra Jo; Myoung Wha Hong; Jun Hee Lee; Young-Yul Kim; Young-Sam Cho (Tissue Engineering and Regenerative Medicine, 2014)

Bridging Disciplines, Knowledge Systems and Cultures in Pest Management - Will Allen; Shaun Ogilvie; Helen Blackie; Des Smith; Shona Sam; James Doherty; Don McKenzie; James Ataria; Lee Shapiro; Jamie MacKay; Elaine Murphy; Chris Jacobson; et al. (Environmental Management, 2014)

Fabrication of 3D alginate scaffold with interconnected pores using wire-network molding technique - Se-Hwan Lee; A. Ra Jo; Ghi Pyoung Choi; Chang Hee Woo; Seung Jae Lee; Beom-Su Kim; Hyung-Keun You; Young-Sam Cho (Tissue Engineering and Regenerative Medicine, 2013)

Common Reasons for “For-Cause” Inspections in Bioequivalence Studies Submitted to the Food and Drug Administration - Bing V. Li; Barbara M. Davit; Christina H. Lee; Santhosh K. Pabba; Chitra Mahadevan; Hoainhon T. Caramenico; Sam H Haidar; Aida L. Sanchez; Aaron W. Sigler; Ethan M. Stier; Dale P. Conner (The AAPS Journal, 2013)

Synergistic Effect and Antibiofilm Activity Between the Antimicrobial Peptide Coprisin and Conventional Antibiotics Against Opportunistic Bacteria - In-sok Hwang; Jae-Sam Hwang; Ji Hong Hwang; Hyemin Choi; Eunjung Lee; Yangmee Kim; Dong Gun Lee (Current Microbiology, 2013)

PM10 data assimilation over south Korea to Asian dust forecasting model with the optimal interpolation method - Eun-Hee Lee; Jong-Chul Ha; Sang-Sam Lee; Youngsin Chun (Asia-Pacific Journal of Atmospheric Sciences, 2013)

Physical explanation of the weakened brightness temperature difference signal over the yellow sea during a dust event: Case study for March 15–16, 2009 - Byung-Ju Sohn; Hyoung-Wook Chun; Hwan-Jin Song; Young-Chan Noh; Sang-Moo Lee; Sang-Sam Lee; Youngsin Chun (Asia-Pacific Journal of Atmospheric Sciences, 2013)

Numerical simulation and evaluation of Asian dust events observed in Mongolia in spring 2011 - Eun-Hee Lee; Erdenebayar Munkhtsetseg; Seung-Bum Kim; Jong-Chul Ha; Sang-Sam Lee; Youngsin Chun (Asia-Pacific Journal of Atmospheric Sciences, 2013)

Implementation of a Reference-Scaled Average Bioequivalence Approach for Highly Variable Generic Drug Products by the US Food and Drug Administration - Barbara M. Davit; Mei-Ling Chen; Dale P. Conner; Sam H. Haidar; Stephanie Kim; Christina H. Lee; Robert A. Lionberger; Fairouz T. Makhlouf; Patrick E. Nwakama; Devvrat T. Patel; Donald J. Schuirmann; Lawrence X. Yu (The AAPS Journal, 2012)

Associations of IFITM3 haplotypes with rheumatoid arthritis in a Korean population - Sam-Youn Lee; Ji-In Yu; Soo-Cheon Chae (Genes & Genomics, 2012)

Soluble HSPB1 regulates VEGF-mediated angiogenesis through their direct interaction - Yoon-Jin Lee; Hae-Jun Lee; Seo-hyun Choi; Yeung Bae Jin; Ho Jung An; Jin-Hyoung Kang; Sam S. Yoon; Yun-Sil Lee (Angiogenesis, 2012)

Study on Evaporation Characteristics of a Sessile Drop of Sulfur Mustard on Glass - Hyunsook Jung; Sung Min Myung; Myung Kyu Park; Hae Wan Lee; Sam Gon Ryu (Bulletin of Environmental Contamination and Toxicology, 2012)

Identification of functional BrFAD2-1 gene encoding microsomal delta-12 fatty acid desaturase from Brassica rapa and development of Brassica napus containing high oleic acid contents - Jin Hee Jung; Hyojin Kim; Young Sam Go; Saet Buyl Lee; Cheol-Goo Hur; Hyun Uk Kim; Mi Chung Suh (Plant Cell Reports, 2011)

Overexpression of AtATM3 in Brassica juncea confers enhanced heavy metal tolerance and accumulation - Mohammed Shafi Ullah Bhuiyan; Sung Ran Min; Won Joong Jeong; Sayeda Sultana; Kwan Sam Choi; Youngsook Lee; Jang R. Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Polyoxygenated ergostane-type sterols from the liquid culture of Ganoderma applanatum - So Young Lee; Ju Sun Kim; Sanghyun Lee; Sam Sik Kang (Natural Product Research, 2011)

Enhancement of xylitol production by attenuation of intracellular xylitol dehydrogenase activity in Candida tropicalis - Byoung Sam Ko; Dong-Min Kim; Byoung Hoon Yoon; Suk Bai; Hyeon Yong Lee; Jung Hoe Kim; Il-Chul Kim (Biotechnology Letters, 2011)

Polymorph Transformation in Paracetamol Monitored by In-line NIR Spectroscopy During a Cooling Crystallization Process - In-Chun Wang; Min-Jeong Lee; Da-Young Seo; Hea-Eun Lee; Yongsun Choi; Woo-Sik Kim; Chang-Sam Kim; Myung-Yung Jeong; Guang Jin Choi (AAPS PharmSciTech, 2011)

Overexpression of a yeast cadmium factor 1 (YCF1) enhances heavy metal tolerance and accumulation in Brassica juncea - Mohammed Shafi Ullah Bhuiyan; Sung Ran Min; Won Joong Jeong; Sayeda Sultana; Kwan Sam Choi; Won Yong Song; Youngsook Lee; Yong Pyo Lim; Jang R. Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

An effect of light emitting diode (LED) irradiation treatment on the amplification of functional components of immature strawberry - Byeong Sam Kim; Hye Ok Lee; Ji Young Kim; Ki Hyun Kwon; Hwan Soo Cha; Jong Hoon Kim (Horticulture, Environment, and Biotechnology, 2011)

OsPRA1 plays a significant role in targeting of OsRab7 into the tonoplast via the prevacuolar compartment during vacuolar trafficking in plant cells - Jae Bok Heo; Woo Young Bang; Se Won Kim; Sung Min Hwang; Young Sim Son; Chak Han Im; Biswa R. Acharya; Chul Wook Kim; Sam Woong Kim; Byung Hyun Lee; Jeong Dong Bahk (Planta, 2010)

Erratum to: On the relationship between ozone and its precursors in the Pearl River Delta: application of an observation-based model (OBM) - Hairong Cheng; Hai Guo; Xinming Wang; Sam M. Saunders; S. H. M. Lam; Fei Jiang; Tijian Wang; Aijun Ding; Shuncheng Lee; K. F. Ho (Environmental Science and Pollution Research, 2010)

Seed-expressed casein kinase I acts as a positive regulator of the SeFAD2 promoter via phosphorylation of the SebHLH transcription factor - Mi Jung Kim; Young Sam Go; Saet Buyl Lee; Youn Sung Kim; Jeong Sheop Shin; Myung Ki Min; Inhwan Hwang; Mi Chung Suh (Plant Molecular Biology, 2010)

Constitutive expression of CaSRP1, a hot pepper small rubber particle protein homolog, resulted in fast growth and improved drought tolerance in transgenic Arabidopsis plants - Eun Yu Kim; Young Sam Seo; Hanna Lee; Woo Taek Kim (Planta, 2010)

Inhibitory effect of Jeju endemic seaweeds on the production of pro-inflammatory mediators in mouse macrophage cell line RAW 264.7 - Eun-Jin Yang; Ji-Young Moon; Min-Jin Kim; Dong Sam Kim; Chan-Shick Kim; Wook Jae Lee; Nam Ho Lee; Chang-Gu Hyun (Journal of Zhejiang University-SCIENCE B, 2010)

Ecklonia stolonifera inhibits lipopolysaccharide-induced production of nitric oxide, prostaglandin E2, and proinflammatory cytokines in RAW264.7 macrophages - Eun-Jin Yang; Young-Min Ham; Dong Sam Kim; Ji-Young Kim; Jung Pyo Hong; Min-Jin Kim; Ji-Young Moon; Wook Jae Lee; Nam Ho Lee; Chang-Gu Hyun (Biologia, 2010)

On the relationship between ozone and its precursors in the Pearl River Delta: application of an observation-based model (OBM) - Hairong Cheng; Hai Guo; Xinming Wang; Sam M. Saunders; S. H. M. Lam; Fei Jiang; Tijian Wang; Aijun Ding; Shuncheng Lee; K. F. Ho (Environmental Science and Pollution Research, 2010)

Antibacterial activity of novel naphthoquiones derivatives - Yongseog Chung; Ren shu Quan; Hyeon Mo Chang; Soo Han Kwon; Soon-Ja Kim; Young-Sam Im; Kyeong Seob Shin; Kyung-Do Park; Hak-Kyo Lee; Joong-Kook Choi (Genes & Genomics, 2009)

Enhanced Benthic Nutrient Flux During Monsoon Periods in a Coastal Lake Formed by Tideland Reclamation - Seok-Hwi Kim; Kangjoo Kim; Minhyung Lee; Hwa-Jin Jeong; Won-Jang Kim; Jong-Gyu Park; Jae-sam Yang (Estuaries and Coasts, 2009)

Cloning and characterization of a gene encoding ABP57, a soluble auxin-binding protein - Keunpyo Lee; Myung-Il Kim; Yu-Jihn Kwon; Minkyun Kim; Yong-Sam Kim; Donghern Kim (Plant Biotechnology Reports, 2009)

Voltammetric Bioassay of Caffeine using Sensor Implant - Suw Young Ly; Chang Hyun Lee; Young Sam Jung (NeuroMolecular Medicine, 2009)

Antimicrobial effect and resistant regulation of Glycyrrhiza uralensis on methicillin-resistant Staphylococcus aureus - Ji-Won Lee; Young-Ju Ji; Mi-Hee Yu; Mi-Hyang Hwang Bo; Hwa-Jeong Seo; Sam-Pin Lee; In-Seon Lee (Natural Product Research, 2009)

A mu opioid receptor gene polymorphism (A118G) and naltrexone treatment response in adherent Korean alcohol-dependent patients - Sung-Gon Kim; Cheol-Min Kim; Sam-Wook Choi; Young-Myo Jae; Hae-Gook Lee; Bong-Ki Son; Jeong-Gee Kim; Young-Sung Choi; Han-Oh Kim; Seong-Yeon Kim; David W. Oslin (Psychopharmacology, 2009)

Inhibition of the CXCR4/CXCL12 chemokine pathway reduces the development of murine pulmonary metastases - Su Young Kim; Chih Hung Lee; Brieanne V. Midura; Choh Yeung; Arnulfo Mendoza; Sung Hyeok Hong; Ling Ren; Donald Wong; Walter Korz; Ahmed Merzouk; Hassan Salari; Hong Zhang; et al. (Clinical & Experimental Metastasis, 2008)

Bioequivalence Approaches for Highly Variable Drugs and Drug Products - Sam H. Haidar; Barbara Davit; Mei-Ling Chen; Dale Conner; LaiMing Lee; Qian H. Li; Robert Lionberger; Fairouz Makhlouf; Devvrat Patel; Donald J. Schuirmann; Lawrence X. Yu (Pharmaceutical Research, 2008)

Distribution and early life history of Kaupichthys leptocephali (family Chlopsidae) in the central Indonesian Seas - Tae Won Lee; Michael J. Miller; Hak Bin Hwang; Sam Wouthuyzen; Katsumi Tsukamoto (Marine Biology, 2008)

Mercury-tolerant Transgenic Poplars Expressing Two Bacterial Mercury-metabolizing Genes - Young Im Choi; Eun Woon Noh; Hyo Shin Lee; Mu Seok Han; Jae Soon Lee; Kwan Sam Choi (Journal of Plant Biology, 2007)

Polymorphism and Genomic Structure of the A+T-Rich Region of Mitochondrial DNA in the Oriental Mole Cricket, Gryllotalpa Orientalis (Orthoptera: Gryllotalpidae) - Iksoo Kim; So Young Cha; Mi Ae Kim; Young Shin Lee; Kwang Sik Lee; Yong Soo Choi; Jae Sam Hwang; Byung Rae Jin; Yeon Soo Han (Biochemical Genetics, 2007)

Desorption characteristics of kaolin clay contaminated with zinc from electrokinetic soil processing - Myung Ho Lee; Masashi Kamon; Soo Sam Kim; Jai-Young Lee; Ha Ik Chung (Environmental Geochemistry and Health, 2007)

Microarray analysis of apple gene expression engaged in early fruit development - Young-Pyo Lee; Gyung-Hee Yu; Young Sam Seo; Sang Eun Han; Yeon-Ok Choi; Daeil Kim; Il-Gin Mok; Woo Taek Kim; Soon-Kee Sung (Plant Cell Reports, 2007)

Comparison of trabecular bone anisotropies based on fractal dimensions and mean intercept length determined by principal axes of inertia - Won-Jin Yi; Min-Suk Heo; Sam-Sun Lee; Soon-Chul Choi; Kyung-Hoe Huh (Medical & Biological Engineering & Computing, 2007)

Chloroplast-targeted BrMT1 (Brassica rapa type-1 metallothionein) enhances resistance to cadmium and ros in transgenicatabidopsis plants - Sun Ha Kim; Hyun Sook Lee; Won Yong Song; Kwan Sam Choi; Yoonkang Hur (Journal of Plant Biology, 2007)

Effect of l-carnitine supplementation and aerobic training on FABPc content and β-HAD activity in human skeletal muscle - Jang Kyu Lee; Jong Sam Lee; Hyon Park; Youn-Soo Cha; Chung Su Yoon; Chang Keun Kim (European Journal of Applied Physiology, 2006)

Alteration of the substrate specificity of Thermus caldophilus ADP-glucose pyrophosphorylase by random mutagenesis through error-prone polymerase chain reaction - Hosung Sohn; Yong-Sam Kim; Un-Ho Jin; Seok-Jong Suh; Sang Chul Lee; Dae-Sil Lee; Jeong Heon Ko; Cheorl-Ho Kim (Glycoconjugate Journal, 2006)

Fruit ripening-related expression of a gene encoding group 5 late embryogenesis abundant protein inCitrus - Oh-Sung Jeon; Chan-Shick Kim; Sam-Pin Lee; Sung Ku Kang; Chang-Myung Kim; Bong-Gyoon Kang; Yoonkang Hur; In-Jung Kim (Journal of Plant Biology, 2006)

Drug expectancy is necessary for stimulus control of human attention, instrumental drug-seeking behaviour and subjective pleasure - Lee Hogarth; Anthony Dickinson; Sam B. Hutton; Nieke Elbers; Theodora Duka (Psychopharmacology, 2006)

An efficient and novel plant selectable marker based on organomercurial resistance - Young Im Choi; Eun Woon Noh; Hyo Shin Lee; Mu Seok Han; Jae Soon Lee; Kwan Sam Choi (Journal of Plant Biology, 2005)

A Cuticle Protein Gene from the Japanese Oak Silkmoth, Antheraea yamamai: Gene Structure and mRNA Expression - Bo Yeon Kim; Nam Sook Park; Byung Rae Jin; Bong Hee Lee; Su Il Seong; Jae Sam Hwang; Jong Su Chang; Sang Mong Lee (Biotechnology Letters, 2005)

Cloning and characterization of the Cu,Zn superoxide dismutase (SOD1) cDNA from the mole cricket, Gryllotalpa orientalis - Iksoo Kim; Kwang Sik Lee; Young Soo Choi; Jae Sam Hwang; Hung Dae Sohn; Byung Rae Jin (Biotechnology Letters, 2005)

Effect of exercise training on muscle glucose transporter 4 protein and intramuscular lipid content in elderly men with impaired glucose tolerance - Hyo Jeong Kim; Jong Sam Lee; Chang Keun Kim (European Journal of Applied Physiology, 2004)

cDNA cloning and mRNA expression of LIM protein gene homologue from the silkworm, Bombyx mori - Jae-Sam Hwang; Hyun-Jeong Go; Tae-Won Goo; Eun-Young Yun; Kwang-Ho Choi; Su-Il Seong; Jong-Su Chang; Sang-Mong Lee; Bong-Hee Lee; Ik-Soo Kim; Nam Soon Kim; Taehoon Chun; et al. (Biotechnology Letters, 2004)

Aerosol Optical and Radiative Properties Observed at Anmyeon and Jeju, Korea in the Spring of 2000 and 2001 - Sung-Nam Oh; Byung-Ju Sohn; Sang-Sam Lee (Environmental Monitoring and Assessment, 2004)

Stable hepatocyte transplantation using fibrin matrix - So-Jung Gwak; Dongho Choi; Seung Sam Paik; Eun Yeol Lee; Kwang Soo Lee; Byung-Soo Kim (Biotechnology Letters, 2004)

Cloning, expression and characterization of a β-agarase gene from a marine bacterium, Pseudomonas sp. SK38 - Nam-Young Kang; Yong-Lark Choi; Young-Su Cho; Beom-Kyu Kim; Beong-Sam Jeon; Jae-Young Cha; Cherol-Ho Kim; Young-Choon Lee (Biotechnology Letters, 2003)

cDNA cloning and mRNA expression of l-3,4-dihydroxyphenylalanine decarboxylase gene homologue from the silkworm, Bombyx mori - Jae-Sam Hwang; Seok-Woo Kang; Tae-Won Goo; Eun-Young Yun; Jin-Sung Lee; O-Yu Kwon; Taehoon Chun; Yuriko Suzuki; Haruhiko Fujiwara (Biotechnology Letters, 2003)

Short-term Changes of Community Structure of Phytoplankton in Summer Around Namhae Island of Korea - Wol Ae Im; Chang Geun Gang; Suk Yang Kim; Sam Geun Lee; Hak Gyun Kim; Ik Gyo Jeong (Algae, 2003)

Induction of pepper cDNA encoding a lipid transfer protein during the resistance response to tobacco mosaic virus - Chang-Jin Park; Ryoung Shin; Jeong Mee Park; Gil-Je Lee; Jin-Sam You; Kyung-Hee Paek (Plant Molecular Biology, 2002)

Cloning of the fibroin gene from the oak silkworm, Antheraea yamamai and its complete sequence - Jae-Sam Hwang; Jin-Sung Lee; Tae-Won Goo; Eun-Young Yun; Kwang-Sik Lee; Yong-Sung Kim; Byung-Rae Jin; Sang-Mong Lee; Keun-Young Kim; Seok-Woo Kang; Dong-Sang Suh (Biotechnology Letters, 2001)